Improvement of concrete characterization using nanomaterials: state-of-the-art - Alghrairi, Nashat; N. Aznieta, Farah; M. Ibrahim, Amer; Wan Hu, Jong; Mohammed Najm, Hadee; Anas, S. M. (John Wiley and Sons, 2025)
The utilization of nanomaterials in concrete has undergone extensive research to enhance its properties. Nanosilica (NS), nanoalumina, nanometakaolin (NMK), nanoclay (NC), and nanocarbon dioxide have demonstrated the ability to improve the compressive strength of concrete at different ages, with a more pronounced impact on early strength. This study aims to systematically analyze the influence of nanomaterial additions on concrete properties, including strength, durability, and resistance to environmental factors. Noteworthy improvements and challenges associated with nanomaterial usage are highlighted. In our findings, the incorporation of various nanomaterials resulted in a notable enhancement of compressive strength, ranging between 12% to 50% when compared to the reference mixture. Nanosilica, nano–titanium oxide, nanoalumina, nano-CaCO3, NC, and nanocarbons were investigated for their potential to increase flexural (2%–22%) and tensile (16%–55%) properties of cement and concrete. Moreover, combining nanomaterials and polypropylene fibers in concrete exhibited enhanced flexural, tensile, and compressive strength, along with improved split tensile strength and bond strength of reinforcement bars. The exploration of composite nanomaterials further demonstrated the capacity to elevate tensile properties, achieving high ultimate tensile strength and precise prediction accuracy. The unique properties of nanomaterials position them as superior alternatives to traditional materials, showcasing applicability in future construction endeavors. Continued research endeavors are anticipated to provide greater reliability and address significant challenges within the building and construction sector.